Problem pomiaru efektywności systemu rachunkowości przedsiębiorstwa - Bujak, Adam (The Problem of Efficiency Measurement of the Enterprise's Accounting System, 2007)
Enterprises that operate in a competitive market should constantly control the efficiency of all activities that they perform. A checking of the effectiveness applies to the accounting system as well. The article presents selected problems concerning the measurement of the efficiency in the accounting system and it shows methods that could be used to do that.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 59-66